EVALUASI PROSES BELAJAR MAHASISWA DALAM AKUNTANSI BIAYA DENGAN STRATEGI PENINJAUAN KEMBALI “HOLLY-WOOD SQUARES” - Marwanto Marwanto; Lewi Patabang (Pusat P2M Politeknik Negeri Batam, 2017)
The research conducted by Marwanto and Patabang, Lewi was aimed to examine the judicial review strategy “Hollywood Square” application in the process of both the cost classification and cost accounting system in odd semester 2016/2017. Data obtained was from the participation of the semester III students of Accounting Department Samarinda State Polytechnic. The result showed that the students’ learning performance increased in every cycle. The pre-test results was 0% of minimum score 71 but pst-test result was 75.53%. The observation result about the lecturer skill in managing the learning with the Judicial Review Strategy “Hollywood Square” with range 1 -4 showed Good Score with the average cycle I and cycle II as much as 3.5. Moreover, the student interest, the activity as well as the teamwork in the learning process with range 1-4 was Good (3.58). The score was the average of all observed aspects in these two cycle. Keywords: evaluation, comprehension, Hollywood Square